Design of a Single-Layer Filtering Patch Antenna with High Gain - Wang, Zhonggen; Gui, Hao; Nie, Wenyan; Yang, Ming; Li, Chenlu (Progress in electromagnetics research C Pier C, 2025)
This paper presents a novel and compact single-layer patch filtering antenna with excellent out-of-band rejection performance. The antenna adopts a simple structure consisting of a single-layer substrate, a slot-loaded radiating patch, and a ground plane, and is fed by a coaxial probe. The rectangular radiating patch and ground plane are loaded with [GAMMA]- anti-[GAMMA]-, and U-shaped slots to form the final design. The introduction of these slots successfully generates two resonance points, which extend the operating bandwidth. It also produces two out-of-band radiation nulls that enhance the out-of-band rejection performance. To validate the proposed design, antenna prototypes were fabricated and measured. The simulation and measurement results are consistent. The antenna exhibits stable realized gain and excellent bandpass response. It achieves a peak realized gain of 8.82 dBi, an impedance bandwidth of 12.8%, and out-of-band rejection greater than 21.26 dB. These characteristics make the proposed patch antenna highly suitable for various wireless communication applications.